Kameloh Baru Village: A Case Study on the Impacts of Unlicensed Gold Mining on the Local Economy and the Environment Use - Nor Anisa (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2023)
This study aims to determine the positive and negative externalities of Illegal gold mining activities of Kameloh Baru Village, Sabangau District, Palangka Raya City. This study uses primary and secondary data with data collection techniques carried out by observation, questionnaires and literature searches with a total of 125 respondents. The analytical method used is the non-parametric Wilcoxon test with SPSS 25 software which provides research results which can be concluded that there are positive and negative externalities in society. The research results show that; (1) There is a positive externality, namely an increase in people's income, that is, there is a difference before the mine and after the mine where the community's income has increased. As well as the level of education costs for children or family members of the community has also increased where the number of children attending school has increased, apart from increased public awareness, this has also been matched by the ability of the community to finance their children's education due to increased community income. (2) While the negative externalities that exist are the health, safety and environment of the people affected by gold mining activities resulting in increased health costs incurred by the community, decreased security conditions around the area, and river water pollution as a result of illegal gold mining